2015
DOI: 10.1038/eye.2015.240
|View full text |Cite
|
Sign up to set email alerts
|

Serial evaluation of retinal vascular changes in infants treated with intravitreal bevacizumab for aggressive posterior retinopathy of prematurity in zone I

Abstract: Purpose To evaluate the serial changes in retinal vasculature in infants treated with intravitreal bevacizumab (IVB) for aggressive posterior retinopathy of prematurity (APROP) in zone I. Methods Retrospective analysis of serial changes in retinal vasculature after IVB in the seven eyes of four babies with APROP in zone I. Results The initial regression, following IVB, was dramatic with reduction in vessel caliber and marked thinning and invisibility of the bridging shunts. Resurgent vascular development was v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…reported three phases of vascular changes following IVB in eyes with zone I ROP mainly phase 1: rapid regression of plus disease; phase 2: slow vascular development and lastly, phase 3: there may be complete regression on follow-up or progression to rebound/recurrent ROP. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…reported three phases of vascular changes following IVB in eyes with zone I ROP mainly phase 1: rapid regression of plus disease; phase 2: slow vascular development and lastly, phase 3: there may be complete regression on follow-up or progression to rebound/recurrent ROP. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 35 ] However, various studies on IVI in infants with ROP have reported the safety of injection at 1 mm, 1.5 mm as well as 2 mm from the limbus. [ 10 15 36 37 ] The current survey shows 51.1% of respondents injecting IVI at 1 mm from the limbus, and a nearly equal number (41.9%) injecting at 1.5 mm from the limbus.…”
Section: Discussionmentioning
confidence: 75%
“…Padhi et al examined changes in retinal vasculature after IVB for APROP in zone 1 and showed a rapid decrease of disease activity within a week of injection followed by a low phase of vascular development. On continued observation, ROP in eyes treated with laser regressed in an expected pattern within 3 weeks, as compared with bevacizumab-treated eyes where peripheral vascular abnormalities persisted even up to 1 year [18]. Lepore et al reported a series of 12 infants with type 1, zone 1 ROP who were treated with IVB in one eye and conventional laser in the fellow eye.…”
Section: Structural Changesmentioning
confidence: 94%